Show me the money: the business models of Linux players. (2nd March 2009) - Migdow, Roger; Sengupta, Sanjit; Verma, Sameer
The major trends characterising the development of e-business platforms include increasing the performance-to-price ratio of hardware components (e.g., servers and chips), as well as the declining costs of operating systems and middleware software as organisations switch from expensive proprietary software (e.g., Microsoft Windows) to open source software (e.g., Linux). The unique origins of Linux and open source software require the adoption of new business models to allow key players to sustain themselves long-term. Using a historical review of the open software movement and a value chain analysis for the open software industry, we examine, using primary data from interviews, the business models of five Linux players (Red Hat, Novell, Navica, Open Country and SohoLaunch). Case analyses enable us to identify four open source business models that should be sustainable in the long run.